Krščanski imperij in cerkvena zgodovina - Petrič, Matej (Ars et humanitas, 2022)
The paper deals with the Church history, which Rufinus of Aquileia, a prominent Christian author of the late 4th and early 5th centuries, wrote after the Goths in-vaded northern Italy in 401/402. It was partly a translation of the Church history of Eusebius of Caesarea to which Rufinus added an appendix in two books describing the events of 325–395. I will attempt to show in what way Rufinus followed in this appendix the conventions and themes set forth by Eusebius, providing several illus-trations of Rufinus’ writing procedure. The key concerns are Rufinus’ representation of the apostolic succession of bishops, his biographical interests, representation of heresy, the suffering of the Jews, pagan persecution and the expansion of Christianity both outside and within the empire, encompassing the conversion of foreign pagans and the fight against local Roman paganism in Egypt and Italy. Rufinus’ appendix is something quite different form Eusebius’ work. Gone are the numerous quotations of sources, which lend Eusebius’ work an air of impartiality and authenticity. Instead Rufinus’ appendix is based to a large degree on oral sources. Rufinus also displays a deep interest in the miraculous, making his appendix a veritable treasure trove of small and large miracles performed by Christians. All this serves his purpose of showing how God is in fact the one pulling the strings behind historical events, and thus orthodox pro-Nicene Christians always prevail against heretics and pagans, since they have the one true God on their side.
Keywords: Christianization; Church history; Eusebius Caesariensis; heresies; herezije; paganism; poganstvo; pokristjanjevanje; Rufinus Aquileiensis